Role of serotonin in physiology and diseases of gastro-intestinal tract - E. F. Barinov; O. N. Sulayeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze the information published in scientific literature on a role of serotonin in regulation of structural homeostasis of gastro-intestinal tract (GIT) organs, realizations of compensatory-adaptive and pathological processes at ulcerogenesis in gastroduodenal zone.Original positions. Enterochromaffin cells and intramural neurons of GIT are main source of serotonin in the body. At analysis of pathogenesis of atopic/allergic diseases it is important to take into account mast cells releasing serotonin as well. The secreted serotonin is accumulated in platelets and released at aggregation. It determines its involvement in pathogenesis of the diseases related to disorders of motility, microcirculation, inflammation and disregeneration. Authors discuss receptor-specific effects of serotonin on blood-tissue barriers of GIT, synaptic transmission, regulation of local and systemic afferentation, motility of the stomach and intestine, and mechanisms of defense. Immunomodulating role of serotonin realized by modulation of cytokine secretion of dendritic cells and lymphocytes is demonstrated.